Electron beam formation and its effect in novel plasma-optical device for evaporation of micro-droplets in cathode arc plasma coating - Goncharov, A.A.; Maslov, V.I.; Naiko, L.V. (Вопросы атомной науки и техники, 2016)
The additional pumping of energy into arc plasma flow by the self-consistently formed radially directed beam of high-energy electrons for evaporation of micro-droplets is considered. The radial beam appears near the inner cylindrical surface by secondary ion - electron emission at this surface bombardment by peripheral arc plasma flow ions. The beam is accelerated by electric potential jump, appeared in a cylindrical channel of the plasma-optical system in crossed radial electrical and longitudinal magnetic fields. The high-energy electrons pump, during the time of micro-droplet movement through the system, the energy, which is sufficient for evaporation of micro-droplets.